Transcranial Direct Current Stimulation to Enhance Cognitive Impairment in Parkinson's Disease: A Systematic Review and Meta-Analysis - Suarez-García, Diana M. A.; Grisales-Cárdenas, Johan S.; Zimerman, Máximo; Cardona, Juan F. (Frontiers in Neurology, 2020)
Cognitive deficits are increasingly being recognized as a common trait in Parkinson's disease (PD). Recently, transcranial direct current stimulation (tDCS) has been shown to exert positive effects as an adjunctive therapy on motor and non-motor symptoms in PD. This systematic review and meta-analysis aims to provide an overview of reported evidence on the efficacy of tDCS interventions in the treatment of cognitive impairments in PD. A systematic literature review was conducted to examine articles that were published in the past 10 years and that study the effects of tDCS on cognitive deficits in PD patients. The PubMed, Scopus and Scielo databases were searched. Eight tDCS studies involving 168 participants were included for the analysis. Our meta-analysis results showed that anodal tDCS (atDCS) had various levels or no evidence of effectiveness. In the pre-post stimulation analysis, a strong effect was reported for executive functions (pre-post: g = 1.51, Z = 2.41, p = 0.016); non-significant effects were reported for visuospatial skills (pre-post: g = 0.27, Z = 0.69, p = 0.490); attention (pre-post: g = 0.02, Z = 0.08, p = 0.934), memory (pre-post: g = 0.01, Z = 0.03, p = 0.972) and language (pre-post: g = 0.07, Z = 0.21, p = 0.832). However, in the pre-follow-up stimulation analysis, the duration of the effect was not clear. This study highlights the potential effectiveness of atDCS to improve cognitive performance in PD patients but failed to establish a cause-effect relationship between tDCS intervention and cognitive improvement in PD. Future directions and recommendations for methodological improvements are outlined.